The effectiveness of phytosomal curcumin on clinical and laboratory parameters of patients with multiple trauma admitted to the intensive care unit: a double-blind randomized placebo-controlled trial - Mahdiye Mirjalili; Amirhossein Sahebkar; Shirin Hassanizadeh; Zahra Kiani; Davood Soleimani; Sepide Amini; Babak Alikiaii; Seyed Adel Moallem; Gholamreza Askari; Saeed Abbasi; Mohammad Bagherniya (BMC Complementary Medicine and Therapies, 2024)
Abstract Background Multiple trauma has serious complications, which increases the risk of morbidity and mortality in the patients. This study aimed to evaluate the impact of supplementation with phytosomal curcumin on clinical and laboratory factors in critically ill patients with multiple trauma. Methods In this double-blind trial, 53 patients with multiple trauma, who were admitted to the intensive care unit (ICU) were randomized to receive either 2 capsules, each capsule containing 250 mg phytosomal (a total of 500 mg daily) as an intervention group or 2 identical capsules (placebo capsules), each containing 250 mg maltodextrin for 7 days. Clinical and laboratory were parameters assessed before and after the intervention. Results After seven days of intervention, the mean increase from baseline in the Glasgow coma scale (GCS) score was significantly higher in the curcumin compared with the placebo group (P-value: 0.028), while the reduction in the APACHE-II score in the curcumin group was greater than that the placebo group in a marginally non-significant fashion (P-value: 0.055). Serum total bilirubin (P-value: 0.036) and quantitative C-reactive protein (CRP) (P-value: 0.044) levels significantly decreased while potassium (P-value: 0.01) significantly increased in the curcumin compared with the placebo group. Moreover, supplementation with phytosomal curcumin significantly increased platelet count (P-value: 0.024) as compared with placebo. The 28-day mortality rate was 7.7% (n: 2 patients) and 3.7% (n: 1 patients) in the placebo and curcumin groups, respectively (P-value > 0.05). Conclusion Phytosomal curcumin had beneficial effects on several clinical and laboratory factors including GCS, APACHEII, serum total bilirubin, CRP, and platelet count in ICU-admitted patients with multiple trauma. Trial registration IRCT20090306001747N1, Available on: https://www.irct.ir/trial/52692 . The first registration date was 12/01/2021.